An Analysis of Conversational Implicature In “Materialists” Movie In 2025 - Vina Ismatul Maula; Evi Pebri Ila Rachma (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the types of conversational implicature and their processess used by the main character in the film “Materialists” (2025). This study applied Yule’s (1996) theory of conversational implicature, which classifies the types of Conversational Implicature into generalized Conversational Implicature and particularized Conversational Implicature. A qualitative method was employed to describe and interpret the utterances of Lucy Mason that reflect Types of Converstionl Implicature and Processes of Conversational Implicature. The results show that out of 34 data, 16 utterances are categorized as generalized conversational Implicature and 18 as particularized conversational implicature. Regarding processes, there are 10 data of PP, 11 of II, and 13 of IR. The findings indicate that generalized conversational implicature appears more frequently, while Indirect Illocution and Interpersonal Rhetoric are the most dominant processess. This study demonstrates that dialogues in the film convey complex implied meanings that depend on context and social interaction among characters.